2014
DOI: 10.1002/jlcr.3246
|View full text |Cite
|
Sign up to set email alerts
|

Convenient synthesis of 18F‐radiolabeled R‐(−)‐N‐n‐propyl‐2‐(3‐fluoropropanoxy‐11‐hydroxynoraporphine

Abstract: Aporphines are attractive candidates for imaging D2 receptor function because, as agonists rather than antagonists, they are selective for the receptor in the high affinity state. In contrast, D2 antagonists do not distinguish between the high and low affinity states, and in vitro data suggests that this distinction may be important in studying diseases characterized by D2 dysregulation, such as schizophrenia and Parkinson’s disease. Accordingly, MCL-536 (R-(−)-N-n-propyl-2-(3-[18F]fluoropropanoxy-11-hydroxyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 46 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…Apomorphine analogs, 11 C-NPA in PET studies of nonhuman primates clearly showed binding to the caudate-putamen, similar to that found for 11 C-raclopride (Finnema et al, 2009; Hwang et al, 2005). More recently, agonists 18 F-MCL-524, apomorphine analogs (Finnema et al, 2014; Sromek et al, 2014) and 18 F-aminomethylchroman analogs (Shalgunov et al, 2015a,b) have been reported for imaging dopamine D2 and D3 receptors. 11 C-PHNO is a modified aminotetralin derivative and has high-affinity for D2 and D3 receptor subtypes thus suggesting that PHNO binds to D2-high affinity state (HA) and D3 receptors.…”
Section: | Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apomorphine analogs, 11 C-NPA in PET studies of nonhuman primates clearly showed binding to the caudate-putamen, similar to that found for 11 C-raclopride (Finnema et al, 2009; Hwang et al, 2005). More recently, agonists 18 F-MCL-524, apomorphine analogs (Finnema et al, 2014; Sromek et al, 2014) and 18 F-aminomethylchroman analogs (Shalgunov et al, 2015a,b) have been reported for imaging dopamine D2 and D3 receptors. 11 C-PHNO is a modified aminotetralin derivative and has high-affinity for D2 and D3 receptor subtypes thus suggesting that PHNO binds to D2-high affinity state (HA) and D3 receptors.…”
Section: | Introductionmentioning
confidence: 99%
“…Therefore, selective D2 and D3 receptor imaging agents will be more useful in evaluating efficacy of treatment regimens. Development of selective agents have been actively pursued; successful aminotetralin‐based, piperazine‐based, apomorphine‐based compounds have been reported (e.g., Mach et al, ; Mukherjee et al, ; Shi et al, ; Sromek et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We have developed an aporphine agonist, R-(−)-2-(3fluoropropanoxy-11-hydroxy-N-n-propyl(1,2-[ 3 H])noraporphine [ 3 H]MCL-536, which binds with high affinity to dopamine D2 receptors but not to other receptors of the D2 family. 31 Additionally, MCL-536 exhibited no affinity or low affinity for other receptors tested, including serotonin, αand βadrenergic, benzodiazepine, GABAA, muscarinic, sigma, kappa, and mu opioid receptors, as well as dopamine, serotonin, and norepinephrine transporters and translocator proteins (NIMH, Psychoactive Drug Screening Program, North Carolina). Herein, we describe the further characterization of this novel agonist ligand with regard to its binding affinities to human D2 receptors expressed in Chinese hamster ovary (CHO) cells.…”
mentioning
confidence: 99%
“…23 MCL-536 is an aporphine agonist that binds with high affinity to dopamine D 2 receptors but not to other receptors of the D 2 receptor family. 24,25 MCL-536 also exhibits little to no affinity for other receptors found in the brain. 25 MCL-536 has a high affinity for the D 2 receptor in its active state, with a K d value of 0.8 nM and K i values of 0.16 nM for (R)-(−)-N-npropylnorapomorphine (NPA) and 0.9 nM for raclopride, respectively, in competition binding assays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have synthesized a highly promising high affinity dopamine D 2 receptor ligand, R -(−)-2-(3-fluoropropanoxy-11-hydroxy-N- n -propyl­(1,2-[ 3 H])­noraporphine ([ 3 H]­MCL-536), as a potential tritiated radioligand for applications in receptor binding assays and autoradiography studies in vitro . MCL-536 is an aporphine agonist that binds with high affinity to dopamine D 2 receptors but not to other receptors of the D 2 receptor family. , MCL-536 also exhibits little to no affinity for other receptors found in the brain . MCL-536 has a high affinity for the D 2 receptor in its active state, with a K d value of 0.8 nM and K i values of 0.16 nM for ( R )-(−)- N - n -propylnorapomorphine (NPA) and 0.9 nM for raclopride, respectively, in competition binding assays …”
Section: Introductionmentioning
confidence: 99%